1992
DOI: 10.1007/bf00012847
|View full text |Cite
|
Sign up to set email alerts
|

The effects of herbicides and mycoparasites at different moisture levels on carpogenic germination in Sclerotinia sclerotiorum

Abstract: Two similar inclined boxes were constructed differing in several aspects from one developed earlier to regulate soil moisture potential. Each box had six 10-cm wide compartments with a perforated plastic cover. Boxes were placed in a room held at 10°C with a RH of 90%. The differential perforations in the plastic that covered the soil surface regulated evaporation which in turn regulated soil moisture. One box was used to carry out experiments on five herbicides at different matric potentials while the other b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
1
0
3
Order By: Relevance
“…The difference in the sclerotial infection at low water potential by the three C. minitans isolates appears to be correlated to their conidial germination at low matric potential, especially at À1.9 MPa, with germination of LU545 being higher than LU112, and T5R42i being intermediate. Similar overall results were reported by Teo et al (1992) where a C. minitans isolate completely inhibited carpogenic germination of sclerotia incubated in soil adjusted to a range of water potentials from À0.01 to À1.5 MPa, although no apothecia were observed at water potentials below À0.7 MPa in the untreated control. For the related pathogen, Sclerotinia minor, decreasing water potential from 0 to À0.1 MPa resulted in an increase in C. minitans infection (Partridge et al 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The difference in the sclerotial infection at low water potential by the three C. minitans isolates appears to be correlated to their conidial germination at low matric potential, especially at À1.9 MPa, with germination of LU545 being higher than LU112, and T5R42i being intermediate. Similar overall results were reported by Teo et al (1992) where a C. minitans isolate completely inhibited carpogenic germination of sclerotia incubated in soil adjusted to a range of water potentials from À0.01 to À1.5 MPa, although no apothecia were observed at water potentials below À0.7 MPa in the untreated control. For the related pathogen, Sclerotinia minor, decreasing water potential from 0 to À0.1 MPa resulted in an increase in C. minitans infection (Partridge et al 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Huang & Erickson (2008) reported that two soil moisture treatments, dry at 9 % and wet at 24 % moisture levels, had no effect on sclerotial parasitism by a C. minitans isolate. Similarly, Teo et al (1992) demonstrated that a C. minitans isolate completely inhibited carpogenic germination of S. sclerotiorum sclerotia incubated in soil at water potentials between 0 and À1.5 MPa, but since no viability assessments were carried out it was unclear whether this was due to reduction in viability of sclerotia or inhibition of germination by C. minitans. Infection of sclerotia of the related pathogen, S. minor, by a C. minitans isolate was reported to increase as soil moisture level decreased from 0 to À100 kPa (0 to À0.1 MPa) (Partridge et al 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Εκτός από το γένος Trichoderma, σε πειράματα in vitro αξιολογήθηκαν επίσης οι ανταγωνιστικοί για το είδος S. sclerotiorum μικροοργανισμοί: Gliocladium roseum (Whipps, 1987), G. virens (Whipps & Budge, 1990;Mukherjee et al, 1995a), Coniothyrium minitans (Tribe, 1957;Whipps & Budge, 1990;Teo et al, 1992;McQuilken et al, 1997), και Trichothecium roseum (Huang & Kokko, 1993).…”
Section: παράγοντες βιολογικής καταπολέμησης: διερεύνηση ενός μοντέλου αλληλεπίδρασηςunclassified
“…Εκτός από το γένος Trichoderma, σε πειράματα in vitro αξιολογήθηκαν κατά των σκληρωτίων του S. sclerotiorum οι ανταγωνιστικοί μικροοργανισμοί: G. roseum (Whipps, 1987b), G. virens (Whipps & Budge, 1990;Mukherjee et al, 1995), C. minitans (Tribe, 1957;Whipps & Budge, 1990;Teo et al, 1992;McQuilken et al, 1997), και T. roseum (Huang & Kokko, 1993). Σε πειράματα in vivo αξιολογήθηκαν οι μικροοργανισμοί C. minitans (Huang, 1980;Trutman et al, 1980;Bogdanova et al, 1986;Krutova, 1987;Whipps & Budge, 1992;Budge et al, 1995;, G. catenulatum (Huang, 1980;Krutova, 1987), T. flavus (Luth et al, 1992), D. elegans (McCredie & Sivasithamparam, 1985, S. sclerotivorum και T. oligocladum (Uecker et al, 1980;.…”
Section: επιδραση του T Koningiiunclassified
“…Ein solcher Mechanismus ist ebenso bei Raps vorstellbar, allerdings ist der Radius, in dem das Myzel eines Sklerotiums eine Pflanze infizieren kann, begrenzt. Willetts und Wong (1980) Coniothyrium minitans, dessen antagonistische Wirkung gegenüber S. sclerotiorum bereits des Öfteren demonstriert werden konnte (Bennett et al 2005), (Jones und Whipps 2002), (Gerlagh et al 1996), (Gerlagh et al 1999), (Teo et al 1992), (Trutmann et al 1980) 25 bis 35% der gesamten Rapsanbaufläche in den späten 80igern und frühen 90igern mit dieser Sorte bestellt , obwohl es sich um eine erucasäureund glukosinolathaltige Sorte handelt. Als Grund hierfür wird vor allem die gute Resistenz gegenüber Sklerotinia genannt.…”
Section: Pflanzenmaterialsunclassified